ChemInform Abstract: Silver‐Catalyzed Decarboxylative Azidation of Aliphatic Carboxylic Acids. Issue 8 (February 2016) - Zhu, Yuchao; Li, Xinyao; Wang, Xiaoyang; Huang, Xiaoqiang; Shen, Tao; Zhang, Yiqun; Sun, Xiang; Zou, Miancheng; Song, Song; Jiao, Ning
Abstract: This novel decarboxylative azidation method is successfully applied to a number of tertiary, secondary, and primary aliphatic carboxylic acids.